Towards a Kantian theory of philosophical education and wisdom: With the help of Hannah Arendt. Issue 6 (16th December 2021) - Varden, Helga
Abstract: Kant's life shows us that it is possible to be a philosopher who revolutionises our thinking about morality in terms of freedom—in fact, to be the first to propose that treating others morally is to treat them with respect or as having dignity—while simultaneously dehumanising himself and others. It presumably follows from this that we can teach our students Kant's brilliant theories of morality as freedom without, thereby, giving them access to all the philosophical resources they need to become wise, good people. In fact, having access to philosophical education can make us unhappy, arrogant or alienated from ourselves, others and society. Helpful to remedying this problem in Kant's philosophy is to bring it into conversation with Hannah Arendt on the topics of human nature and philosophical education within the context of modern life. Together, their theories also bring to light sources of emotional challenges that make it more difficult to achieve wisdom. Indeed, I suggest, Kant's own failures at achieving wisdom are not accidentally related to these challenges—as are those of much ideal theory today.